2021
DOI: 10.3390/su131910913
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors for Throwing in Competition in Male Elite Handball

Abstract: The aims of this study were to define determinant factors that affected throwing actions used to score goals in handball, and to study the effectiveness of throwing actions and their relationships with different factors during their use, such as: the throwing distance, type of arm build, type of throw, whether it is done while jumping or while supported, the last supporting foot and the previous step cycle, as well as their relationship with the final score of the game in elite male handball competitions. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
1
3
0
1
Order By: Relevance
“…Even back players, that are supposed to throw from long distances, showed a frequency of just 22.5%. The results are similar to those obtained by other studies [ 28 , 30 , 31 ], very far from the data provided by Eftene et al [ 32 ] that estimate remote shots to be around 45.66%. These differences may be due to the registration system based on direct observation, compared to the registration through technological resources used in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even back players, that are supposed to throw from long distances, showed a frequency of just 22.5%. The results are similar to those obtained by other studies [ 28 , 30 , 31 ], very far from the data provided by Eftene et al [ 32 ] that estimate remote shots to be around 45.66%. These differences may be due to the registration system based on direct observation, compared to the registration through technological resources used in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…Another relevant issue of this study is to verify that more than 80% of the throws in all positions are made at high or very high speeds (categories 3 and 4). In the same line, Tuquet et al [ 31 ], who analyzed 1049 throws of a high-level men’s championship, found that more than 95% of the throws were made at the highest possible speed compared to only 5% that were ability shots. Regarding effectiveness, the wings are the most effective players with 62% and 64% (LW and RW respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the distance shots quantity decrease, significantly more center area 6-meter actions are performed. It needs to be emphasized that creating a 6-meter scoring chance is tactically linked with the distance shoot threat made by the backcourt players in order to open the space for pivot player activity or/and fainting activity for the rest of court players [21,22]. Analyzing the level of differences in the number of actions performed at EHF EURO 2020 and 2022, clear tendency in implementing the tactics aimed to finalize the actions from as close distance to the goal as possible was found.…”
Section: Discussionmentioning
confidence: 99%
“…Por otra parte, se encontró una similitud con los resultados de 24 partidos de balonmano masculino de elite entre los años 2018 y 2020 (Tuquet et al, 2021) donde los lanzamientos desde la zona de 6 metros (en este estudio agrupados en los lanzamientos de zona del pivote y central y lateral sin oposición) fueron más eficaces que los de 9 metros (zona central y lateral con oposición). Del mismo modo, hubo una semejanza con los datos de la selección femenina de Rumania U19 que compitió en el Campeonato Europeo del 2013 y presentó una eficacia de los 7 metros del 80%, de los lanzamientos de 9 metros del 44% y de los 6 metros (pivote) del 74% (Acsinte y Alexandru, 2014).…”
Section: Resultsunclassified